FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENCEGAHAN COVID-19 PADA MASYARAKAT DI KECAMATAN ABELI KOTA KENDARI TAHUN 2021 - Dian Ramadani; Jumakil Jumakil; Jusniar Rusli Afa (Endemis Journal, 2021)
Covid-19 is a new type of disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2), Transmission is very easy and rapid spread so Covid-19 must be cut off the chain of transmission by paying attention to the prevention of Covid-19. Its rapid spread throughout the world including Indonesia claimed many lives, which who designated it as the Covid-19 pandemic. Implementas above will not be maximized if not supported by community compliance with the policy. This community's compliance can be influenced by a variety of factors, namely knowledge, family support and the role of health workers. The purpose of this study is to find out the factors related to covid-19 prevention compliance in the community in Abeli District, Kendari City in 2020. The type of research used is observational analytics using cross sectional study design. The population in this study is people aged 12-60 years who live in Abeli subdistrict with a total of 18,041 respondents, the sample in this study amounted to 379 respondents, sampling using proportional random sampling techniques. The data was analyzed univariately and bivariate using Chi square test. The results of the study at a confidence level of 95%, showed there is a link between knowledge (ρValue = 0.002) family support (ρValue = 0.000) the role of health worker (ρValue = 0.000) with Covid-19 prevention compliance. In conclusion, there is still the need to increase efforts to prevent Covid-19 to suppress the transmission of the virus.